Pengaruh Pemberian Cookies Daun Kelor Terhadap Peningkatan Berat Badan Balita Usia 1-5 Tahun: The Effect of Giving Moringa Leaf Cookies on Weight Increasing Toddler Age 1-5 Years - Selasih Putri Isnawati Hadi; Nirma Susanti; Febry Heldayasari (Journal of Health, 2024)
Based on electronic data from Community-Based Nutrition Recording and Reporting in November 2022, the prevalence of stunted toddlers in Posyandu was 36.8%, malnutrition was 18% and toddlers not gaining weight was 52%. Toddlers are a critical period whose nutrition must be considered for optimal growth and development. This can be helped by optimizing the use of natural ingredients that are easily available, one of which is the use of Moringa leaves as a food innovation for toddlers. The aim of this research is to analyze the effect of giving cookies with the addition of Moringa powder on increasing the weight of toddlers aged 1-5 years. The research method uses a Quasy Experiment with a pretest and posttest approach with control group design. Research subjects were toddlers aged 1-5 years who met the criteria. The sample used purposive sampling of 36 respondents. Data analysis uses univariate analysis and to test the influence between two variables using the Man Whitney Test. By using the Man Whitney test, the p-value was 0.003<0.05, meaning there was a difference in giving Moringa leaf cookies to the increase in body weight of toddlers aged 1-5 years. The conclusion of this research is that there is an effect of giving moringa leaf cookies on increasing the weight of toddlers aged 1-5 years, this is because the moringa content is very complete and can help increase the weight of toddlers.